2017
DOI: 10.1021/jacs.7b06772
|View full text |Cite
|
Sign up to set email alerts
|

N-Heterocyclic Carbene-Stabilized Boranthrene as a Metal-Free Platform for the Activation of Small Molecules

Abstract: The multielectron reduction of small molecules (e.g., CO) is a key aspect of fuel synthesis from renewable electricity. Transition metals have been researched extensively in this role due to their intrinsic redox properties and reactivity, but more recently, strategies that forego transition metal ions for p-block elements have emerged. In this vein, we report an analogue of boranthrene (9,10-diboraanthracene) stabilized by N-heterocyclic carbenes and its one- and two-electron oxidized congeners. This platform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
65
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 42 publications
1
65
0
4
Order By: Relevance
“…CO reduction under mild conditions,a lbeit not always in ac atalytic fashion. [14] In the meantime, related systems have been disclosed by Kinjo [15,16] and Harman [17] and shown to add CO 2 through one of its C=O bonds (D-F;S cheme 1b). Follow-up reactions with various reducing agents have been studied and the palette of obtainable compounds encompasses CO,H C(O)OH, H 3 COH, and CH 4 .…”
mentioning
confidence: 99%
“…CO reduction under mild conditions,a lbeit not always in ac atalytic fashion. [14] In the meantime, related systems have been disclosed by Kinjo [15,16] and Harman [17] and shown to add CO 2 through one of its C=O bonds (D-F;S cheme 1b). Follow-up reactions with various reducing agents have been studied and the palette of obtainable compounds encompasses CO,H C(O)OH, H 3 COH, and CH 4 .…”
mentioning
confidence: 99%
“…[6] Among them, only ahandful of boroncontaining heteroarenes have been shown to activate small molecules in reactions taking place at the boron centers under mild conditions ( Figure 1). [7][8][9][10] Theg roups of Wagner and Holthausen reported on the use of the dianionic 9,10diboraanthracene I for H 2 activation. [7] Harman and coworkers showed that the neutral N-heterocyclic carbene stabilized 9,10-diboraanthracene II undergoes [4+ +2] cycloaddition reactions with O 2 ,c arbon dioxide (CO 2 ), and ethylene.…”
mentioning
confidence: 99%
“…[7] Harman and coworkers showed that the neutral N-heterocyclic carbene stabilized 9,10-diboraanthracene II undergoes [4+ +2] cycloaddition reactions with O 2 ,c arbon dioxide (CO 2 ), and ethylene. [8] Our group has demonstrated that 1,3,2,5-diazadiborinine III reacts with CO 2 ,c arbonyl compounds,a lkenes, and alkynes in af ormal [4+ +2] cycloaddition. [9] We have also isolated the annulated 1,4,2,5-diazadiborinine derivative IV, which not only reacts with non-activated unsaturated bonds, such as C = O, C = C, C C, and C Nb onds,b ut also cleaves C À O, B À H, Si À H, and P À Hbonds.…”
mentioning
confidence: 99%
“…[13] Theresulting complex (4), showing methylation of the carbon atom linking the phosphine and NHC moieties, was isolated as am ixture of two diastereomers (ratio 6:1) differing by the position of the methyl group with respect to the iodine atom (Scheme 2, middle). Fort his purpose,c omplex 2 was first treated with KHMDS followed by the addition of an excess of classical alkylating agent such as MeI.…”
mentioning
confidence: 88%